Coaching As Determinant of Job Performance: Co-working Support As Mediating Variable - Tri Wijayati, Dewie; Fazlurrahman, Hujjatullah; Kholidi Hadi, Hafid; Rahman, Zainur; Kautsar, Achmad (KnE Social Sciences, 2020)
Employees become movers in all types of businesses. Good or bad depends on the job performance of its employees. Therefore, managers are currently starting to discuss investments that consist of coaching for employees. Intense inter-company relations, so that inter-company relations will affect his work and will have an impact on his Job performance. For the sake of hope is to improve employee performance and development. the purpose of the research is to find out the effect of coaching on the job performance that is moderated by co-worker support. This study discusses the relationship between providing coaching to XYZ employee job performance in a company that is moderated by co worker support. This study will explore the exploration of training provided to employees. The sample size of this study is 80 employees and author use PLS (Partial Least Square) to measure the research model. The results of the study explain significant coaching on job performance. However, mentoring is moderated by the support of coworkers is not significantly approved for job performance. Keywords: Coaching, Co-working support and job performance